The Effect of Learning Strategies and Cognitive Styles on Learning Outcomes of Mathematics after Controlling Intelligence - Robby Rezeki; Harun Sitompul; Julaga Situmorang (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to determine the differences in learning outcomes of mathematics subjects between groups of students who are taught with modified inquiry learning strategies and guided inquiry that has a cognitive style after being controlled by intelligence. This research method uses quasi-experimental with 2 x 2 factorial design The research sample consisted of 80 people, each consisting of 1 (one) class of 40 students, both students of Senior High School  5 Stabat and 40 students of Senior High School  1 Stabat. Hypothesis testing results show that: (1) student learning outcomes in mathematics taught with modified inquiry free learning strategies are better than mathematics learning outcomes of students taught with guided inquiry learning strategies after controlling intelligence, (2) learning outcomes of group mathematics students who have FI cognitive style are better than the group of students who have FD cognitive style after controlling intelligence, (3) the effect of interaction between learning strategies and cognitive style on mathematics learning outcomes of students after controlling intelligence, (4) for students who have FI cognitive style obtains better learning outcomes of mathematics learning outcomes if taught with modified free inquiry learning strategies compared to if taught with guided inquiry learning strategies after controlling intelligence.